ANALISIS KINERJA KEUANGAN PEMERINTAH KABUPATEN NAGEKEO TAHUN 2009 – 2013 - HERNI SUNARYA (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
The research was conducted by taking the location of the District Government Office Nagekeo. Object of thisstudy is the Budget Nagekeo District fiscal year 2009 to 2013. Variables used in this study is the ratio of theindependence, effectiveness ratio, the ratio of harmony, growth ratio, the ratio of the proportion of thebudget. Type of used is quantitative such as district budget realization report Nagekeo. The results showedthat the results of the achievement of financial self-sufficiency ratio of the area of the 2009 -2013 assessed isstill lacking because it is on a scale ratio of 0 % - 10 % . Local financial independence with theseachievements are in a relationship pattern instructive, where the dominant role of the central governmentover the independence of local governments that have not been independently assessed local governmentsimplement regional autonomy. Average effectiveness ratio Nagekeo District Revenue was 99.14 % in thecategory are quite effective. There is no harmony between the apparatus and expenditure of publicexpenditure where expenditure is still higher officials of public spending, which the average public spendingNagekeo District during the year 2008 - 2012 is 32.38 % while the average expenditure apparatus NagekeoDistrict during 2009 - 2013 is 67.42 % . This suggests that more attention Nagekeo County Governmentservices to the local and not the emphasis of public services that will be enjoyed directly by the public or thepublic . The average local government revenue growth during the year 2009-2013 Nagekeo by 58.86 % andshowed positive growth